Karakteristik Sosiodemografi dan Kondisi Kesehatan Anak pada Kejadian Stunting Balita - Intan Putri Pitriani; Hani Handayani; Heri Budiawan; Ade Kurniawati; Asep Setiawan (Literasi Intelektual, 2026)
Background: Stunting is a chronic nutritional disorder in children under five and remains a major public health problem in Indonesia. Its occurrence is influenced by various factors, including family sociodemographic characteristics and child health conditions. Objective: This study aimed to examine the association between maternal sociodemographic factors and child health conditions and the incidence of stunting among children under five. Methods: An analytical observational study with a cross-sectional design was conducted. A total of 83 children under five were selected using simple random sampling. Data were collected through structured questionnaires and anthropometric measurements. Statistical analysis was performed using the Chi-square test. Results: Family income was significantly associated with stunting (p = 0.029), with a higher proportion observed among children from families earning below the regional minimum wage. Child age was also significantly associated with stunting (p = 0.012), particularly among those aged 25–48 months. In contrast, maternal age, maternal education, maternal occupation, number of children, and history of infectious diseases were not significantly associated with stunting (p > 0.05). Conclusion: Family income and child age were significantly associated with stunting among children under five.